Profiling Movement and Gait Quality Characteristics in Pre-School Children - Mark Holton (Journal of Motor Behavior, 2018)
There is a dearth of suitable metrics capable of objectively quantifying motor competence. Further, objective movement quality characteristics during free play have not been investigated in pre-school children. The aims of this study were to characterize children's free play physical activity and investigate how gait quality characteristics cluster with free play in pre-school children (3–5 years old). Sixty-one children (39 boys; 4.3 ± 0.7 years, 1.04 ± 0.05 m, 17.8 ± 3.2 kg) completed the movement assessment battery for children and took part in free play while wearing an ankle- and hip-mounted accelerometer. Characteristics of movement quality were profiled using a clustering algorithm. Spearman's rho and the Mann-Whitney U tests were used to assess relationships between movement quality characteristics and motor competence classification differences in integrated acceleration and spectral purity, respectively. Significant differences were found between motor competency classifications for spectral purity and integrated acceleration (p < .001). Spectral purity was hierarchically clustered with motor competence and integrated acceleration. Significant positive correlations were found between spectral purity, integrated acceleration and motor competence (p < .001). This is the first study to report spectral purity in pre-school children and the results suggest that the underlying frequency component of movement is clustered with motor competence.